Work-related Respiratory Symptoms and Associated Factors among Cement Factory Workers in Rupandehi District, Nepal - Poudel, L.; Regmi, S.; Dahal, P.; Ghimire, M.; Nepal, S.; Manandhar, N. (Kathmandu University Medical Journal, 2021)
Background Cement factory workers are exposed to cement dust at workplace. It leads to a greater prevalence of chronic respiratory signs and symptoms. Objective To identify the prevalence of Work-related respiratory symptoms, its association with various risk factors, and to assess the outcomes like hospitalization and sickness absenteeism. Method Cross-sectional study was conducted in the Argakhanchi Cement factory among 190 workers with minimum work experience of 1 year. Census method was used for data collection. To assess the respiratory symptoms, sputum samples were collected; smears prepared by pick and smear method, and later stained by Leishman and pap stain. Smears devoid of alveolar macrophages were considered unsatisfactory for evaluation. Result The mean age of respondents with standard deviation was 35.56±11.45 years. The prevalence of Work-related respiratory symptoms was 31.6%. Age, no. of years worked, working in the raw materials department, burner and clinker department, cleaning department and wearing mask were the significant risk factors. On cytological analysis of the sputum sample, mild inflammatory cell noticed in 71.6%, moderate inflammation in 23.7%, and dense inflammation in 4.2%. Fungal spores were seen in 3.7%, fungal pseudohyphae in 0.5%, and bacterial colonies in 27% of the sputum samples. Out of 190 participants, 8(4.2%) of them had to be hospitalized and 17(8.9%) were on sick leave due to respiratory symptoms. Conclusion Pre-employment and periodic medical examination, frequent work shift, training on occupational health and safety, use of appropriate personnel protective equipment is recommended to reduce respiratory symptoms.